Migration and domestic work : the collective organisation of women and their voices from the city - Yilmaz, Gaye; Ledwith, Sue (Palgrave Macmillan, 2017)
With female migrants dominating low paid and ever-expanding domestic work worldwide, this book brings together the voices of 120 migrating women from 28 different nations and 10 different religious affiliations. Together they tell how patriarchal and religious gender codes in the family and at work shape their new lives in London, Berlin and Istanbul. Through their own accounts, the study explores the intersecting multiple and gendered identities women carry from their home countries and how these are reshaped, challenged, changed, or not, as they encounter different structures, traditions and cultural codes in their new countries. With women?s propensity for collective organizing, whether via community, social movements or trade unions as a central theme, the authors also bring together issues of migration, work and identity with trade union and community organizing.
Keywords: Urban women -- Social conditions.; Women household employees.; Women immigrants.; elektronické knihy; electronic books